A methodology for estimating and evaluating a knowledge management model using structural equations (Orinoquia, 2020)
This article describes a structural equation-based methodology for estimating and evaluating a knowledge management model for testing and estimating causal relationships from statistical data and theoretical references on causality. It highlights the most influential indicators that should be considered for improving knowledge management in the IT area of the Simón University in Barranquilla, based on ICT, intellectual capital, organisational learning and innovation. It demonstrates that the designed instrument was reliable according to Cronbach’s alpha test and was useful for measuring knowledge management regarding the most influential variables. These were ICT (main services and infrastructure), intellectual capital (focusing on structural capital, organisational climate and business processes), organisational learning (cultural system and team learning) and innovation (referring to policies encouraging personal creativity).
Keywords: organisational learning; structural equation; knowledge management; research instrument